The effects of grazing and the meteorologic factors on wind-sand flux in the desert steppe - Meng, Biao; Gao, Cuiping; Lv, Shijie; Han, Guodong; Li, Zhiguo; Li, Junran; Wu, Qian; Zhang, Feng (Frontiers in Environmental Science, 2024)
Global climate warming and other human activities are leading to the degradation of grassland vegetation and wind erosion in arid areas becoming increasingly severe. To understand the impact of variation in grazing intensity on aeolian flux in arid grasslands, we monitored wind-sand flux for three years on an experimental site on the desert steppe of Inner Mongolia. We examined variation in wind-sand flux under different stocking rates with corresponding collection height and climate factors. Overall, we found that the windsand flux was higher when rainfall was low and the stocking intensity was high.Specifically, the wind-sand flux increased 50.3% and 83.6% in the moderate and high grazing treatments as compared to the control. We also found a significant interaction